Facial flushing after thermocoagulation of the Gasserian ganglion. - Drummond, P D (1983)
The development of a facial flush during thermocoagulation of the Gasserian ganglion was monitored in 16 patients with pulse recording techniques and in a further 17 patients with thermography. There was a close association between the development of the facial flush in the distribution of one or more divisions of the trigeminal nerve and the subsequent demonstration of postoperative analgesia. In regions where significant changes took place, vascular pulsations increased 25-233% (mean 96%) and facial temperature rose 0.5-2.0 degrees C. The response persisted for up to an hour postoperatively, and was not diminished in patients with pre-operative analgesia from a previous procedure. Possible mechanisms for the facial flush, including stimulation of an active vasodilator system, the antidromic release of vasoactive substances from trigeminal nerve terminals and the release of tonic vasoconstriction are discussed. A practical application of the pulse recording technique used in the present investigation would be to monitor the distribution of vasodilatation at operation to avoid unwanted first division sensory loss.